Respon Pertumbuhan Anggrek Dendrobium Fase Seedling terhadap Variasi Jenis Media Tanam - Kismayanti, Choirul Nisa; Ulfah, Maria; Rachmawati, Rivanna Citraning (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Orchids are ornamental plants that are very popular with the public and consist of many types of orchids. The aim of this research is to find out how various types of planting media influence the growth of dendrobium orchids. This study was conducted for three months, from May to July 2023. The research used was a Completely Randomized Design (CRD) which consisted of three different types of planting media, namely: M1 (kadaka roots); M2 (wood charcoal); and M3 (Sphagnum moss). Data analysis was carried out using one-way ANOVA and the Lowest Significant Difference (LSD) test at the 5% level. The results of the analysis show that there are differences in the types of planting media used to plant kadaka roots, Sphagnum moss, and wood charcoal. In the planting medium, kadaka roots grow well with high variable stem growth. In the Sphagnum moss planting medium, it gave the best growth in the shoot height increase variable, while in the wood charcoal planting medium it did not show suboptimal growth in terms of stem height, stem diameter, shoot height and number of roots. Sphagnum moss planting medium provides the best growth for increasing shoot height.